2000
DOI: 10.1177/0145445500243003
|View full text |Cite
|
Sign up to set email alerts
|

Cueing, Demand Fading, and Positive Reinforcement to Establish Self-Feeding and Oral Consumption in a Child with Chronic Food Refusal

Abstract: A 3-year-old child with multiple medical disorders and chronic food refusal was treated successfully using a program that incorporated antecedent control procedures combined with positive reinforcement. The antecedent manipulations included visual cueing of a criterion number of self-feeding responses that were required during meals to receive reinforcement and a gradual increase in the imposed criterion (demand fading) that was based on improved frequency of oral consumption. As evaluated in a changing criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 10 publications
1
45
0
4
Order By: Relevance
“…T he research base for treatment of children with feeding disorders ranges from treatments that focus on antecedent manipulations (e.g., ahearn, 2003;Johnson & Babbitt, 1993;Kerwin, ahearn, eicher, & Burd, 1995;Luiselli, 2000) to consequence manipulations. However, most of the research in the treatment of food refusal has largely shown that (a) procedures designed to address negative reinforcement (e.g., nonremoval of the food presented) are often vital for treatment success (Cooper et al, 1995;Reed et al, 2004), and (b) with few exceptions (e.g., Casey, Cooper-Brown, Wacker, & Rankin, 2006;Wilder, Normand, & atwell, 2005), positive reinforcement strategies alone often are insufficient to adequately reduce food refusal and increase bite acceptance.…”
mentioning
confidence: 99%
“…T he research base for treatment of children with feeding disorders ranges from treatments that focus on antecedent manipulations (e.g., ahearn, 2003;Johnson & Babbitt, 1993;Kerwin, ahearn, eicher, & Burd, 1995;Luiselli, 2000) to consequence manipulations. However, most of the research in the treatment of food refusal has largely shown that (a) procedures designed to address negative reinforcement (e.g., nonremoval of the food presented) are often vital for treatment success (Cooper et al, 1995;Reed et al, 2004), and (b) with few exceptions (e.g., Casey, Cooper-Brown, Wacker, & Rankin, 2006;Wilder, Normand, & atwell, 2005), positive reinforcement strategies alone often are insufficient to adequately reduce food refusal and increase bite acceptance.…”
mentioning
confidence: 99%
“…Very few published studies, other than case reports [28,29], have examined the effectiveness of outpatient feeding programs for transitioning children from tube to oral feeding. This may be because of the relative dearth of multidisciplinary feeding programs, because their focus is on clinical care rather than research, and because of the heterogeneity of the patients and their feeding problems.…”
Section: Outpatient Treatmentsmentioning
confidence: 99%
“…One limitation of early studies on extinction of negative reinforcement is that escape extinction was combined with other procedures such as differential reinforcement (Ahearn et al, 1996;Cooper, et al, 1995Hoch et al, 1994Luiselli, 2000;Luiselli & Gleason, 1987); therefore, the individual effects of the procedures on acceptance and inappropriate behavior were not clear. In fact, a careful examination of the literature reveals that there are no studies that we could find that clearly demonstrate the effectiveness of positive reinforcement alone with multiple participants with severe feeding problems.…”
Section: Summary Of Treatment Literaturementioning
confidence: 99%